SPECTROSCOPICAL STUDY OF AN ETHER FRACTION ISOLATE FROM STEAM BARK OF “ JATI” (Tectona grandis, L) - Fredryk Mandey; Raimundus Chalik; Ismail Ibrahim (Universitas Gadjah Mada, 2009)
This research is aimed to primarily study the spectroscopy of ether fraction of from Jati wood (T. grandis, L). The stem bark of T.grandis, L was firstly extracted undergoes a reflux in methanol solvent. Further, the dried methanol crude extract was extracted with diethyl ether and moreover separated its chemical constituents by using of column chromatography using degraded mixtures of n-hexane - ethyl acetate from 9:1 to 7:3. After a final column chromatography from the E fraction, a white needles crystal with a melting point of 295 - 297.5 °C was resulted. This results was then confirmed undergoes a spectroscopic analysis including UV, FTIR, H-NMR, and Mass spectroscopy to get an acid of 3β-hydroxy-20(29)-lupen-28-oic or commonly known as betulinic acid.